2017
DOI: 10.1002/fsn3.512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooking techniques on fatty acid and oxylipin content of farmed rainbow trout (Oncorhynchus mykiss)

Abstract: The aim of this study was to investigate the effect of various cooking techniques on the fatty acid and oxylipin content of farmed rainbow trout. Rainbow trout is an excellent source of long‐chain omega‐3 (n‐3) polyunsaturated fatty acids (PUFA) which have beneficial health effects. Fillets of 2‐year‐old farmed rainbow trout were baked, broiled, microwaved, or pan‐fried in corn (CO), canola (CaO), peanut (PO), or high oleic sunflower oil (HOSO). Fatty acids and oxidized lipids were extracted from these samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…The ∑ω‐3PUFAs in raw FWME muscle was found 13.70%, which was reduced to 10.95%, 7.54%, 11.11%, and 11.11% in grilled, boiled, fried, and microwaved FWME muscles, respectively. Similar results of increasing the SFAs content and decreasing ∑ω‐3PUFAs in fish muscles due to various cooking treatments were reported (Flaskerud et al., 2017; Zhang et al., 2013). Eicosapentaenoic acid, considered as one of the most important fatty acids in fish oil, was found in very poor quantities in raw and cooked FWME muscles, ranging from 0.53% to 0.79%.…”
Section: Resultssupporting
confidence: 83%
“…The ∑ω‐3PUFAs in raw FWME muscle was found 13.70%, which was reduced to 10.95%, 7.54%, 11.11%, and 11.11% in grilled, boiled, fried, and microwaved FWME muscles, respectively. Similar results of increasing the SFAs content and decreasing ∑ω‐3PUFAs in fish muscles due to various cooking treatments were reported (Flaskerud et al., 2017; Zhang et al., 2013). Eicosapentaenoic acid, considered as one of the most important fatty acids in fish oil, was found in very poor quantities in raw and cooked FWME muscles, ranging from 0.53% to 0.79%.…”
Section: Resultssupporting
confidence: 83%
“…Although in this study, cooking oil was not used in the frying process, the reduction of PUFAs in pan-fried salmon may occur if cooking oil is added during frying. Flaskerud et al found that pan-frying trout in corn oil and canola oil had no effect on the level of PUFAs in the fish, but pan-frying with peanut oil and high oleic sunflower oil induced the reduction of EPA and of EPA and DHA, respectively [ 33 ]. This matched the findings from Gladyshev et al, who used sunflower oil to fry the salmon [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipids from the lyophilized sample (0.5 g) were extracted for 3 h using the chloroform-methanol method of Flaskerud et al [2017], and nitrogen was used to limit the exposure to oxygen. Then, the chloroform layer was separated and dried under nitrogen.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%